A Population‐Based Study of the Epidemiology of Chronic Hypoparathyroidism. (30th November 2017) - Vadiveloo, Thenmalar; Donnan, Peter T; Leese, Graham P
ABSTRACT: There are very few reports on the epidemiology of chronic hypoparathyroidism. A population‐based study was undertaken to describe the prevalence and incidence of hypoparathyroidism in Tayside, Scotland. Data on biochemistry, hospital admissions, prescribing, and death records in Tayside, Scotland, from 1988 to 2015 were linked electronically. Patients with at least three serum albumin–corrected calcium concentrations below the reference range that were taken in an outpatient setting were included in the study. Patients with severe chronic kidney disease before low calcium were excluded from the study. Patients with hypocalcemia were included if they had either previous neck surgery/irradiation, a low serum parathyroid hormone (PTH), or were treated with vitamin D. Patients were identified as having either a postsurgical or a nonsurgical cause or had secondary hypoparathyroidism, eg, hypomagnesemia. Overall, 18, 955 patients were identified with hypocalcemia. Of these, 222 patients had primary hypoparathyroidism, 116 with postsurgical and 106 with nonsurgical chronic hypoparathyroidism. In 2015, the prevalence of primary hypoparathyroidism was 40 per 100, 000, with a rate of 23 and 17 per 100, 000, respectively, for postsurgical and nonsurgical. Eighty percent of the former and 64% of the latter were female. The mean serum calcium at diagnosis was 1.82 mmol/L (SD ± 0.24) and the annual incidence varied from 1–4 per 100, 000. Overall, 71% of patients were prescribed vitamin D and/or calcium, whereas activated vitamin D was used in 48% of postsurgical cases and 43% of nonsurgical cases. Thyroxine and/or hydrocortisone were prescribed in more than 90% of postsurgical and 64% of nonsurgical cases. In conclusion, the prevalence of nonsurgical chronic hypoparathyroidism was greater than previously reported using this population‐based approach. Many had mild hypocalcemia and did not receive any treatment. © 2017 American Society for Bone and Mineral Research.